REDE DE PROTEÇÃO A MULHERES VÍTIMAS DA LEI MARIA DA PENHA - Hasse, Bárbara Gusso; Do Santos, Elisângela Maria Almeida; Santos, Bruna Oliveira; Piber, Lizete Dieguez; Piber, Lizete Dieguez (Salão do Conhecimento, 2018)
XIX Jornada de Extensão